2007
DOI: 10.1089/vbz.2006.0520
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of Abundance and Lassa Virus Prevalence in Mastomys natalensis in Guinea, West Africa

Abstract: Based on empiric surveillance data, the incidence of human Lassa fever (LF) cases in Guinea and other West African countries has been reported to increase during the dry season compared to the rainy season. To investigate possible links with the ecology of the rodent reservoir of the virus, we conducted a 2-year longitudinal survey of Mastomys natalensis in a region of high human Lassa virus (LASV) seropositivity in Guinea. Standardized rodent trapping with similar trapping efforts between seasons was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
157
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(174 citation statements)
references
References 27 publications
1
157
0
2
Order By: Relevance
“…In Mali, Granjon et al (2005b) found M. huberti in the inner delta of Niger and in south Mali and it is known in wet zones of S. Senegal . From our previous works in North East Guinea and Central Guinea, M. natalensis and M. erythroleucus are recorded in the same villages but never M. huberti (Denys et al 2005b;Lecompte et al 2006;Fichet-Calvet et al 2007). In the Nimba region, Gautun et al (1986) described two morphs but failed to attribute them and no karyotypes were Figure 12.…”
Section: Mastomys Species Distribution In West Guineamentioning
confidence: 89%
“…In Mali, Granjon et al (2005b) found M. huberti in the inner delta of Niger and in south Mali and it is known in wet zones of S. Senegal . From our previous works in North East Guinea and Central Guinea, M. natalensis and M. erythroleucus are recorded in the same villages but never M. huberti (Denys et al 2005b;Lecompte et al 2006;Fichet-Calvet et al 2007). In the Nimba region, Gautun et al (1986) described two morphs but failed to attribute them and no karyotypes were Figure 12.…”
Section: Mastomys Species Distribution In West Guineamentioning
confidence: 89%
“…However, we also found the occurrence of LF in August indicating that infection potentially can occur at any time of the year. Similarly, in Guinea, as in other West African countries, LF is known to occur throughout the year but is more common in the dry season due to higher numbers of M. natalensis in homes due to restricted food supply (22). …”
Section: Discussionmentioning
confidence: 99%
“…The significance of these contacts in terms of LASV transmission depends on their frequency and on the proportion of M. natalensis in the catch, i.e., on the number of M. natalensis caught and eaten. Ecological studies in Guinea suggest that M. natalensis is predominantly found in houses and proximal cultivations, but infrequently in distal cultivations (Fichet-Calvet et al 2007), thus consumption of M. natalensis might be less important relative to other rodents. The potential in variation to LASV exposure along a geographically induced behavioral gradient (consumption of bush rats vs. non-consumption of town rats), as well as preference and avoidance of certain species, provides a strong argument to investigate human behaviors as drivers for disease emergence (Kock 2014) and their overlay with the eco-epidemiology of zoonotic diseases and reservoir species.…”
Section: Discussionmentioning
confidence: 99%